Transvaginal natural orifice transluminal endoscopic surgery (vNOTES) in gynecological emergencies - Rafael Ferro; Yannick Hurni; Stéphanie Seidler; Daniela Huber (Elsevier, 2023)
Objective: Transvaginal natural orifice transluminal endoscopic surgery (vNOTES) is an emerging minimally invasive approach increasingly applied to perform many gynecological procedures. Despite a still limited level of evidence, compared to conventional laparoscopy, vNOTES seems to be associated with reduced blood loss, shorter operative time, less postoperative pain, shorter hospitalization time, better cosmetic results and decreased postoperative morbidity. Although growing evidence supports the effectiveness of vNOTES for elective adnexal surgeries, there is still limited knowledge regarding its feasibility and safety in emergency settings. In the present study, we report our experience performing vNOTES in gynecological emergency cases. Study design: We prospectively collected and analyzed data from patients who underwent vNOTES for gynecological emergencies between November 2021 and June 2023. Demographic and perioperative characteristics were collected and analyzed. Results: Seventeen patients were included. Interventions were realized for suspicion of ectopic pregnancy in 7 cases (41.2%), for suspicion of adnexal torsion in 7 cases (41.2%), for post-hysterectomy hemoperitoneum in 2 cases (11.8%), and for uncontrollable uterine bleeding in 1 case (5.9%). Emergency procedures included unilateral salpingectomy (35.3%), ovarian cystectomy (23.5%), ovarian cystotomy (17.6%), adnexal detorsion (11.8%), hemoperitoneum drainage (11.8%), hysterectomy (5.9%), and appendectomy (5.9%). The overall median operative time was 38 [18-72] minutes. The median estimated intraoperative blood loss was 30 [5−150] mL, and no intraoperative complications occurred. Conversion to conventional laparoscopy or laparotomy was never needed. Patients stayed hospitalized for a median time of 30 [4−144] hours after the intervention. The median visual analog scale value for postoperative pain evaluation was 2 [0−5] at 12, 24, and 48 postoperative hours. No complications associated with the procedure occurred. Conclusions: This study demonstrated the feasibility of performing vNOTES procedures for managing gynecological emergencies such as tubal ectopic pregnancy, adnexal torsion, painful ovarian lesions, post-hysterectomy hemoperitoneum, and uncontrollable uterine bleeding. Associated with data reported in the available literature, our results suggest potential benefits in treating gynecological emergencies by vNOTES over conventional laparoscopy. However, stronger evidence from larger studies is needed to confirm it.